Green and sustainable tapioca-derived carbon dots immobilised on screen printed electrode for detection of heavy metals using electrochemical method - Pudza, Musa Yahaya (2020)
The environment is increasingly polluted by heavy metals and myriads of harmful contaminants that cause irreversible damage to living things. Reliable measurement and detection of pollutants can minimize heavy metal pollution, this can be accomplished through the adoption of carbon dots (CDs). Biomass waste has been the popular choice of CDs source, but it can be contaminated due to its nature (i.e sourced from waste). To improve the sensitivity and accuracy of a rapid detection or measurement of heavy metals pollution, the need for CDs with greater purity and structural homogeneity from a clean source such as tapioca cannot be overemphasized. Herein, CDs were synthesized from tapioca by a hydrothermal process based on Photoluminescent quantum yield (PLQY). Variables such as temperature, dosage, time, and amount of solvent were explored. CDs synthesis further explored the application of response surface methodology (RSM) and subsequent development of artificial neural network (ANN) platform for achieving reliable and efficient CDs. Characterization of the optimized CDs was done by atomic force microscopy (AFM), high-resolution transmission microscopy (HRTEM), energy dispersive spectroscopy (EDS), X-ray photoelectron spectroscopy (XPS), and zeta potential. The sensitive and simultaneous detection of a ternary mixture of cadmium (Cd2+), lead (Pb2+), and copper (Cu2+) in an aqueous solution was successful by utilizing modified SPCE/AuNP/CDs electrode. Modification by gold nanoparticles was undertaken via electrodeposition. Differential pulse voltammetry and cyclic voltammetry were deployed for the analysis of the analytes. A cyclic voltammetry analysis was employed using a potential range between − 0.8 to + 0.2 V at a scan rate of 100 mV/s. Differential pulse voltammetry technique was applied through the electrode for sensitive and selective determination of Cu2+, Pb2+, and Cd2+ at a concentration range of 0.01 to 0.27 ppm. Tolerance for the highest possible concentration of foreign substances such as Mg2+, K+, Na+, NO3 − and SO4 2 − was observed with a relative error of less than ± 3%. The sensitivities of the modified electrode were 0.17, 0.42, and 0.18 ppm/μA for cadmium, lead, and copper, respectively. The limits of detections achieved for cadmium, lead, and copper were 0.0028, 0.0042, and 0.014 ppm respectively. In conclusion, the modified SPCE provides a cost-effective, dependable, and stable means of detecting heavy metal ions (Cu2+, Pb2+, and Cd2+) in an aqueous environment.